The Protective Effects of Kaempferol and Quercetin on Cisplatin-Induced Oxidative Stress and Genotoxicity in Human Peripheral Blood Lymphocytes - Zamani, Ehsan; Evazalipour, Mehdi; Salehy, Mehrnoush Vaez; Kunter, Imge; Ghaffarkandi, Zahra Nahavandi (Iranian Soc Pharmacognosy, 2025)
Background and objectives: Cisplatin is one of the most widely used anti-cancer drugs. Some less well-known side effects, like genotoxicity, are linked to the widespread use of cisplatin. Kaempferol and quercetin are two antioxidant flavonoids. This study aimed to investigate the genotoxicity of cisplatin in human peripheral lymphocytes, as well as the protective effects of quercetin and kaempferol. Methods: The cells were separated into the following groups: cisplatin group (0.8 mu g/mL); treatment quercetin); and control group. DNA damage was evaluated using alkaline comet assay and the cytokinesis-block micronucleus test. Glutathione, malondialdehyde, superoxide dismutase, and catalase levels were also measured as indicators of oxidative stress. Results: The results showed that cisplatin can induce oxidative stress by lowering glutathione, catalase activity, and superoxide dismutase activity and raising lipid peroxidation. The results of genotoxicity assays demonstrated that cisplatin elevated micronucleus frequency in addition to the percentage of DNA in the tail moment of the comet. This study reveals that quercetin and kaempferol decreased micronucleus frequency, the percentage of DNA in the tail and tail moment and lipid peroxidation. Both quercetin and kaempferol increased superoxide dismutase activity; however, only quercetin was able to significantly increase glutathione concentration and catalase activity compared to cisplatin group. Conclusion: It can be concluded that a major contributing reason to cisplatin's genotoxic effects is through oxidative stress. Furthermore, quercetin or kaempferol may help protect human peripheral blood cells from cisplatin-induced genetic damage.
Keywords: cisplatin; comet assay; kaempferol; micronuclei; quercetin